Desmoplastic round small cell tumor: a case report of a neoplasm of difficult diagnosis - Ogata, Daniel Cury (2005)
Desmoplastic Small Round Cell Tumor (DSRCT) is a rare neoplasm of difficult diagnosis, recently described by Gerald et al. There are reports of nearly 101 cases in the literature, being the intra-abdominal region its most common location and children and young adults its preferred age group. This paper reports a case of DSRCT in a young adult of 24 years of age. This patient presented unspecific symptoms of nausea, vomiting and a single episode of hematemesis. Upon physical examination a solid mass on the epigastrium and left hypochondrium was found. Image diagnostic procedures confirmed the existence of the expansive process and also revealed enlarged retroperitoneal lymphonodes. Diagnosis was achieved through videolaparoscopic biopsy. Histologic sections stained with hematoxylin/eosin were inconclusive and immunohistochemical analysis was required to establish the diagnosis. This analysis revealed positivity to epithelial and mesenchimal markers and weak posivity to chromogranin A, characteristic results of DSRCT. Due to the fact that the disease was locally advanced, the patient was treated with chemotherapy (cyclofosfamide and paclytaxel). However, since there was only partial response to the treatment, the patient refused to undergo any second line option of therapy. Presently, the patient is being submitted only to supportive care, within an 18-month follow-up program.